Pimpuri Kandam Biranak: Penyembuhan Secara Tradisional Oleh Kaum Bidayuh Di Kedup, Serian, Sarawak - Clayton, Anak Robert; Ling, How Kee (Institute of Borneo Studies, UNIMAS, 2016)
The studies that had been done by researcher like Hart (1999) and Durie (1996) found that every indigenous society have their own way in giving help to others that been guided by their custom and indigenous knowledge. Applying direct method and practice from western countries when working with the indigenous people might be unsuitable and impractical to them. Hence, it is essential for the adaptation and integration of practice and method with the local existing helping practices by learn valuable lesson from the local helping approaches to develop culturally appropriate with the indigenous society. The aim of this study is to learn and drawing lesson from the traditional healing method that is PKB for the profesion that gives help to develop culturally appropriate practice when working with the indigenous society. This study applied the qualitative method by interviewed informants that rich in experiences for this study from selected kampung in Kedup area under the Serian administration by using purposeful sampling method select informant. The selection of the informants was guided by a purposive sampling in order to give insight data for the study. For the this study, three informant was selected base on the main criteria that is knowledge, skills, experiences in giving help by the pingurik (designated helper) and also the experiences by the informant that ever having kandam biranak before. From the study conducted shows that the PKB is helpful and effective in helping women after post natal period problem. Therefore, from the result of this study illustrate that it is important for the profession that gives help to learn and drawing lesson to integrate and adapt the knowledge from the traditional healing method in their practices.